2019
DOI: 10.1182/blood-2019-130062
|View full text |Cite
|
Sign up to set email alerts
|

Toxicities and Outcomes of Acalabrutinib-Treated Patients with Chronic Lymphocytic Leukemia: A Retrospective Analysis of Real World Patients

Abstract: Introduction: Acalabrutinib (acala) is an irreversible, second generation Bruton tyrosine kinase inhibitor (BTKi) approved by the FDA for the treatment of relapsed/refractory (R/R) mantle cell lymphoma, and is in advanced stages of clinical testing for front line (FL) and R/R CLL (Byrd NEJM, Wang NEJM). Ibrutinib (ibr) is a well-established and potent treatment for CLL; however, discontinuation due to intolerance precludes a significant number of patients (pts) in clinical practice from long-term benefit of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…This also means that in the clinical trials with long follow up, dermatological side-effects are scarce. However, if severe, they are among AEs that lead to ibrutinib discontinuation ( Sharman et al, 2017 ; Mato et al, 2018 ; Yazdy et al, 2019 ). In the retrospective analysis of real-world acalabrutinib-treated CLL patients, intolerant to ibrutinib, it was shown that rash led to discontinuation of ibrutinib in 10 (22%) of 46 patients.…”
Section: Mechanisms Underlying Rashmentioning
confidence: 99%
See 1 more Smart Citation
“…This also means that in the clinical trials with long follow up, dermatological side-effects are scarce. However, if severe, they are among AEs that lead to ibrutinib discontinuation ( Sharman et al, 2017 ; Mato et al, 2018 ; Yazdy et al, 2019 ). In the retrospective analysis of real-world acalabrutinib-treated CLL patients, intolerant to ibrutinib, it was shown that rash led to discontinuation of ibrutinib in 10 (22%) of 46 patients.…”
Section: Mechanisms Underlying Rashmentioning
confidence: 99%
“…However, there are several limitations. At present clinical data from long-term clinical trials or real-world data are only available for a few of the inhibitors, namely for ibrutinib ( Mato et al, 2018 ; Munir et al, 2019 ), acalabrutinib ( Yazdy et al, 2019 ; Sharman et al, 2020 ) and zanubrutinib ( Tam et al, 2019b , 2020a ), but the follow-up time varies among the studies. Thus, the available dataset on AEs is limited for several of the inhibitors such as tirabrutinib ( Sekiguchi et al, 2020 ) or fenebrutinib ( Cohen et al, 2020 ), due to low patient enrollment, short-term trials or that the clinical data have not been published as yet.…”
Section: Brief Introductory Overview To Adverse Effectsmentioning
confidence: 99%
“…70 In a real-world setting involving ibrutinib-intolerant patients treated with acalabrutinib, the ORR was 62% after 5 months follow-up and discontinuation rates due to AEs were similar to those reported by Awan et al (2019). 71 Acalabrutinib combined with anti-CD20 antibody obinutuzumab was studied in a phase 1b/2 study, ACE-CL-003 (NCT02296918), in patients with R/R (n = 26) and treatment-naive CLL (n = 19). 72 At a median follow-up of 39 months in treatment-naive patients and 42 months in patients with R/R CLL, the ORRs were 95% and 92%, respectively.…”
Section: Clinical Studies Of Acalabrutinib In Patients With MCLmentioning
confidence: 99%
“…In a real‐world setting involving ibrutinib‐intolerant patients treated with acalabrutinib, the ORR was 62% after 5 months follow‐up and discontinuation rates due to AEs were similar to those reported by Awan et al . (2019) 71 …”
Section: Acalabrutinib In Cll and MCL Studiesmentioning
confidence: 99%
“…Additionally, retrospective and prospective data show acalabrutinib to be well tolerated in ibrutinib-intolerant patients with CLL. 46 , 47 These results suggest that increased selectivity towards BTK could reduce cardiac toxicity. The phase III ASCEND trial compared acalabrutinib therapy versus investigators choice of idelalisib with rituximab or BR in R/R CLL.…”
Section: Something New: Second Generation Btk Inhibitors Does Selectmentioning
confidence: 89%